CREATIVE APPROACHES TO PREPARING FUTURE PRIMARY SCHOOL TEACHERS FOR PEDAGOGICAL ACTIVITIES - Kamolakhon Abrorxon kizi Abrorxonova; Khadicha Karamatovna Muhammadiyeva; Farit Rafaelovich Yuzlikayev (The Bioscan, 2025)
This article examines, analyzes, and draws conclusions on the theoretical foundations of the creative training of future primary school teachers for pedagogical activities, as well as the content of the concept of pedagogical activity.